Perspectives on European Social Work : From the Birth of the Nation State to the Impact of Globalisation. - Lorenz, Walter (Verlag Barbara Budrich, 2006)
The book offers explanations and clarifications for the bewildering variety of titles and job profiles in the social professions in Europe. It presents them both as a product of specific national welfare arrangements and as a sign of a special kind of professional autonomy that so far helped to correct national welfare trends. Now this autonomy is once more called for in the light of the complete re-structuring of all European welfare states and a European model of social work could deliver impulses for real alternatives to growing exclusion and inequality.